Importance of Execution of Projects 717 and 749 in the Implementation of the LGBTI Public Policy in the Human Bogotá. (2017)
Lesbian, Gay, Bisexual, Transgender and Intersex -LGBTI- people that reside in the city of Bogotá have taken collective actions in order to strengthen their social movement and to reduce discrimination and segregation as barriers to their fundamental rights. Despite the Constitutional provisions of special protection of minorities, multiple human rights abuses occurred on a daily basis, which inspired non-governmental organizations and LGBTI leaders to pursue political advocacy during the governments of Luis Eduardo Garzón, Samuel Moreno and Gustavo Petro, for the LGBT policy formulation and implementation. It should be noted that during the "Bogotá Humana" government, the District Secretariats of Planning and Social Integration made strong administrative and financial efforts through the investment projects 717 and 749, in order to enforce the rights of people with diverse sexual orientation and non-normative gender identities.